Implementasi Metode Agile Untuk Membangun Sistem Informasi Monitoring Kegiatan Santri Berbasis Web Di Pondok Pesantren Nurul Jalal Jakarta - Dewi Syu'ara Nisa; Joko Priambodo (CV. Multi Kreasi Media, 2024)
Pesantren is an educational institution, which accommodates students and is fostered to have the ability, intelligence, and skills to achieve educational goals. Pesantren Nurul Jalal Jakarta is a cottage-based religious education institution that regulates all matters relating to the implementation of religious education. The status of private educational institutions does not make the Nurul Jalal Islamic Boarding School lagging behind other institutions in achieving achievements and also in the application of student discipline. Problems occur in the processing of achievement data, memorization, attendance which is still done manually and has not used automatic data storage (database). In addition, it is necessary to monitor achievement, memorization and attendance to determine the active level of students in terms of achievement, memorization and attendance carried out by the same students continuously. The development of information systems in this study uses the agile software development method. Based on the research to be achieved, this research is expected to have the benefits obtained from this research. . For the Nurul Jalal Islamic Boarding School, this student monitoring system is very important to facilitate the tasks of the teachers at the Nurul Jalal Islamic Boarding School.